2005
DOI: 10.1161/01.atv.0000149381.16166.c6
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Receptor Class B Type I Mediates the Selective Uptake of High-Density Lipoprotein–Associated Cholesteryl Ester by the Liver in Mice

Abstract: Objective-High-density lipoprotein (HDL) cholesteryl esters (CE) are taken up by liver and adrenals selectively, ie, independent from particle internalization. Class B type I scavenger receptor (SR-BI) mediates this uptake in vitro. The role of SR-BI in HDL metabolism was explored in mice. Methods and Results-Mice with a mutation in the SR-BI gene (SR-BI KO) and wild-type (WT) littermates were used.Mutants had increased HDL cholesterol. HDL was labeled with 125 I (protein) and [ 3 H] (CE). After HDL injection,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
100
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 26 publications
13
100
2
Order By: Relevance
“…Abundant data have indicated that, in rodents, SR-B1 is a critical regulator of HDL metabolism [39][40][41] . Presently, the roles of dietary fat in modulating the expression of SR-B1 are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Abundant data have indicated that, in rodents, SR-B1 is a critical regulator of HDL metabolism [39][40][41] . Presently, the roles of dietary fat in modulating the expression of SR-B1 are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Caveolae, cytosol, and internal membranes were isolated using Opti-Prep method as described previously ( 7,8 ). This method generates a highly purifi ed fraction of caveolae that is enriched in caveolin-1 and free of bulk plasma membrane markers.…”
Section: Isolation Of Caveolaementioning
confidence: 99%
“…In SR-BI-deficient mice, HDL selective CE uptake by the liver decreases by more than 90% but HDL holoparticle uptake is unchanged, suggesting that holoparticle uptake does not involve SR-BI. 2,3 A likely candidate mechanism mediating HDL holoparticle uptake in the absence of SR-BI is the cell-surface complex related to mitochondrial F 1 -adenosine triphosphatase (ATPase), namely ecto-F 1 -ATPase. 4 When HDL binds to apolipoprotein A-I (apoA-I), this enzyme generates extracellular adenosine diphosphate (ADP) which then specifically activates the P2Y 13 receptor which is a Gprotein-coupled receptor.…”
mentioning
confidence: 99%